Factitious Disorders and Cardiothoracic Surgery: The Ongoing Multidisciplinary Challenges of a Complex Case. (8th December 2009) - Firstenberg, Michael S.; Sirak, John H.; Sun, Benjamin; Kasick, David P.
Abstract : Chronic factitious disorder, Munchausen's syndrome, can be challenging to manage—particularly when complaints and symptoms suggest medical or surgical emergencies. We present a patient whose problems have spanned many years and a great distance. Hopefully, with a greater awareness of this disease, as this patient continues to seek health care in many different hospitals, the implications of timely access to information, good histories and physical exams, and an index of suspicion can assist in potentially avoiding unnecessary, expensive, and invasive evaluations.